Współczesne relacje międzyludzkie „wołające” o dialog - Ściupider-Młodkowska, Mirosława (Kultura-Społeczeństwo-Edukacja, 2020)
Ściupider-Młodkowska Mirosława, Contemporary interpersonal relations that demand dialogue. Culture – Society – Education no 2(16) 2019, Poznań 2019, pp. 85–93,Adam Mickiewicz University Press. ISSN 2300-0422. DOI10.14746/kse.2019.16.6. The aim of the article is to answer the question of why contemporary interpersonal relationships need dialogue in cultural and social transformations ? The article is based on the conclusions of the author’s research carried out among a selected group of students revealing the characteristics of homo construens. Young people who took part in the research directed (constructed) the scripts of partnership and family biographies as free, original and willing to change. On the other hand, the same scripts unmasked loneliness and a huge need for recognition in the world of cultural and narcissistic demands for self-actualisation, satisfaction and a sense of fulfilment in the spheres of partnerships and family. The need for dialogue requires pedagogical support that will reveal the values of community, social groups and partnerships.